Identification of linear systems with known dynamics of macroeconomic inputs - Борода, Аліна Олександрівна; Назаренко, Олександр Максимович (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2015)
The problem of identification and specification of dynamic input-output model of macroeconomic system. Modeling of phase trajectories and offices held with the cyclicality inherent in macroeconomic processes, and occurs through the allocation of harmonious waves propagating in the system.